Research on the relationship of the weaker enterprises post-merger brand strategy and consumers' purchase intention: Based on the brand authenticity. Issue 1 (3rd September 2018) - Yao, Peng; Wang, Xinxin
Abstract : Purpose: Nowadays, many weak brands have acquired strong international brands to accelerate their internationalization. However, "the weakers acquire the strongers" model of M&A leads to many consumers' loss. The purpose of this paper is to explore the relationships between the brand strategy after the M&A, brand authenticity and consumer purchase intention through two experiments. Design/methodology/approach: Building on an extensive literature review, the authors identify four hypotheses. Hypotheses were tested on data collected across 190 Chinese consumers. Findings: The results show that the decline of consumer purchase intention was mainly caused by the falling consumer assesses on brand authenticity; the different post-merger brand strategies have significant difference on brand authenticity and consumer purchase intention, and self-brand connection played a moderate role between brand authenticity and consumer purchase intention. Originality/value: The research reveals the reasons for consumer loss after mergers and acquisitions and provides empirical insights into how post-merger brand strategies can be manifested to convey brand authenticity as well as to build consumers' purchase intention. In addition, the findings confirm the role of self-brand connection.